High-power short duration vs. conventional radiofrequency ablation of atrial fibrillation: a systematic review and meta-analysis. Issue 5 (1st February 2021) - Ravi, Venkatesh; Poudyal, Abhushan; Abid, Qurrat-Ul-Ain; Larsen, Timothy; Krishnan, Kousik; Sharma, Parikshit S; Trohman, Richard G; Huang, Henry D
Abstract: Aims: We sought to compare the effectiveness and safety of high-power short-duration (HPSD) radiofrequency ablation (RFA) with conventional RFA in patients with atrial fibrillation (AF). Methods and results: MEDLINE, Cochrane, and ClinicalTrials.gov databases were searched until 15 May 2020 for relevant studies comparing HPSD vs. conventional RFA in patients undergoing initial catheter ablation for AF. A total of 15 studies involving 3718 adult patients were included in our meta-analysis (2357 in HPSD RFA and 1361 in conventional RFA). Freedom from atrial arrhythmia was higher in HPSD RFA when compared with conventional RFA [odds ratio (OR) 1.44, 95% confidence interval (CI) 1.10–1.90; P = 0.009]. Acute PV reconnection was lower (OR 0.56, P = 0.005) and first-pass isolation was higher (OR 3.58, P < 0.001) with HPSD RFA. There was no difference in total complications between the two groups ( P = 0.19). Total procedure duration [mean difference (MD) −37.35 min, P < 0.001], fluoroscopy duration (MD −5.23 min, P = 0.001), and RF ablation time (MD −16.26 min, P < 0.001) were all significantly lower in HPSD RFA. High-power short-duration RFA also demonstrated higher freedom from atrial arrhythmia in the subgroup analysis of patients with paroxysmal AF (OR 1.80, 95% CI 1.29–2.50; P < 0.001), studies with ≥50 W protocol in the HPSD RFA group (OR 1.53, 95% CI 1.08–2.18; P = 0.02] and studies with contact force sensing catheter use (OR 1.65, 95% CI 1.21–2.25; P = 0.002). Conclusion: High-power short-duration RFA was associated with better procedural effectiveness when compared with conventional RFA with comparable safety and shorter procedural duration.